The Effect of Communication, Information, and Education (CIE) on Breastfeeding Techniques on the Reduction of Breast Engorgement in the Working Area of ​​Talang Tinggi Community Health Center, Seluma Regency - Entan Afriannisyah; Handayani Handayani; Reni Hariyanti; Kintan Anisa (Jurnal Kebidanan Manna, 2026)
Background : Breast milk dam is a common problem experienced by postpartum women and can interfere with the success of breastfeeding. Inappropriate breastfeeding techniques are one of the factors that can contribute to the occurrence of breast milk dams. Therefore, effective Communication, Information, and Education (IEC) regarding proper breastfeeding techniques is needed to improve mothers' knowledge and skills and prevent breast milk dams. Methods : This study used an analytic survey with a quasi-experimental approach and a two-group pre-test and post-test design. The study involved 32 postpartum women in the working area of Talang Tinggi Health Center, Seluma Regency, who were divided into an experimental group and a control group. The experimental group received IEC on breastfeeding techniques using leaflet media, while the control group received IEC without leaflet media. Data were analyzed using the Wilcoxon Signed Rank Test and Mann-Whitney U Test. Results : The Wilcoxon test showed a significant reduction in the incidence of breast milk dams in the experimental group after the IEC intervention using leaflets (p = 0.004; <0.05). In the control group, the intervention without leaflet media showed a less significant difference (p = 0.034). The Mann-Whitney U Test showed a significant difference between the experimental and control groups in reducing the incidence of breast milk dams (p = 0.001; <0.05). Conclusion: IEC on proper breastfeeding techniques accompanied by leaflet media is effective in reducing the incidence of breast milk dams among postpartum women. Leaflet-based IEC can improve mothers' knowledge and skills in applying correct breastfeeding techniques and may be used as an effective communication and educational strategy in primary health services